2017
DOI: 10.1002/phar.1961
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Oral Antiplatelet Agents in Patients with Acute Coronary Syndrome

Abstract: OBJECTIVE In randomized controlled trials, prasugrel and ticagrelor reduced cardiovascular complications in patients with acute coronary syndrome (ACS) compared with clopidogrel. However, limited head-to-head comparisons have been conducted across the three antiplatelet agents using real-world data. The aim of this study was to compare clinical outcomes of three strategies during a 1-year period after percutaneous coronary intervention (PCI). METHODS Rates of all-cause and acute myocardial infarction (AMI) hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…A retrospective cohort study based on TRUVEN MarketScan claims data that included all patients observed a decreased rate of all‐cause and MI‐related hospital admissions in patients using prasugrel or ticagrelor when compared to clopidogrel irrespective of treatment duration. No difference was noted between prasugrel and ticagrelor; however, the sample size for this comparison was limited (n = 2524 ticagrelor patients and n = 8335 prasugrel patients) …”
Section: Discussionmentioning
confidence: 97%
“…A retrospective cohort study based on TRUVEN MarketScan claims data that included all patients observed a decreased rate of all‐cause and MI‐related hospital admissions in patients using prasugrel or ticagrelor when compared to clopidogrel irrespective of treatment duration. No difference was noted between prasugrel and ticagrelor; however, the sample size for this comparison was limited (n = 2524 ticagrelor patients and n = 8335 prasugrel patients) …”
Section: Discussionmentioning
confidence: 97%
“…11 Ticagrelor provides faster, greater, and more consistent P2Y12 inhibition and reduces more ischemic events in patients undergoing PCI as compared with clopidogrel. 12 PLATO (Study of Platelet Inhibition and Patient Outcomes), a multicenter, randomized, double-blind trial, aimed to determine the superiority of the ticagrelor over clopidogrel in the prevention of vascular events and death in 18,624 patients presenting with ACS. 13 The patients were randomized to receive either ticagrelor (180 mg loading, followed by 90 mg twice daily maintenance dose) or clopidogrel (300-600 mg loading, followed by 75 mg daily maintenance dose) group.…”
Section: Discussionmentioning
confidence: 99%
“…11 Ticagrelor provides faster, greater, and more consistent P2Y12 inhibition and reduces more ischemic events in patients undergoing PCI as compared with clopidogrel. 12…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ticagrelor was released in the United States during the conduct of the TRANSLATE‐ACS study, and was used infrequently by patients enrolled in the study; only 2.1% of patients in the TRANSLATE‐ACS study were treated with ticagrelor at the time of their index event. Practice changes since the TRANSLATE‐ACS study period show a small, but significant, increase in uptake of higher‐potency P2Y 12 inhibitors in the United States, and these data may not fully reflect current practices; however, >50% of patients with ACS are still treated with clopidogrel in many contemporary US registries 8, 38, 39. Last, because patients in the TRANSLATE‐ACS study were only observed for 15 months after the index MI event, we are unable to report outcomes for patients with P2Y 12 inhibitor intensification in response to recurrent events compared with those without intensification.…”
Section: Discussionmentioning
confidence: 99%